Improved Modified Ratio Estimators of Population Mean Based on Deciles - Muhammad Abid (Science Faculty of Chiang Mai University, 2019)
Different population characteristics of the auxiliary variables have so far been employed to develop ratio estimators for estimating population mean of the study variable. This article comprises developing some new modified ratio estimators using the linear combinations of coefficient of variation, population correlation coefficient and deciles of the auxiliary variable. The mean square errors of all the proposed ratio estimators and the efficiency conditionsare also derived. Numerical illustrationshave beenmade to support the findings of the study.From theoretical and numerical findings, it is noted that the proposed estimators are more efficient as compared to all the existing estimators used in this study.